MENCERMATI AKTIVITAS NGAWEN DI JEMBRANA DARI PERSPEKTIF EKOFENIMISME - Wiasti, Ni Made (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Encroachment of protected forest known as ngawen in Jembrana is a violation against the forestry laws, potentially harming the forests and infringing the basic idea of feminism. In that respect, this paper is going to examine the strategies and implications of the activity in the perspective of ecofeminism. In perspective of ecofeminism, it is obvious that ngawen activity is carried out with a strategy reflecting the anthropocentrism and androcentrism. On the one hand, it implicates the increasingly severe destruction of protected forest; while on the other hand, it implies a less equitable gender relation in the domestic socio-economic aspect of the pengawens’ household.
Keywords: Keywords: anthropocentrism, androcentrism, ngawen, forests and gender relations.